The Preparation Hydroxyapatite – Zirconia Composites as Bioceramic Materials - Eneng Maryani; Sri Cicih Kurniasih; Naili Sofiyaningsih; Bayu Priyanto (Balai Besar Keramik, 2018)
Hydroxyapatite (HAP) is a material often used as a bioceramic because of its special characteristics such as has the same mineral composition as the original bone and teeth, does not cause cytotoxic effects, biocompatible, bioactive and promote osteoconductivity. However HAP shows poor mechanical properties so it is less applicable to biological applications that must accept heavy loads. Therefore, it is necessary to modify the hydroxyapatite structure through the process of reinforcement (composite formation) with other materials such as zirconia (ZrO2). In this research, hydroxyapatite – zirconia composite prepared from each component made from local natural mineral. The compositions of prepared hydroxyapatite – zirconia composites are 75:25, 50:50, and 25:75. In all composite compositions prepared after calcination at 1000 oC, hydroxyapatite phase change into whitlockite and tetrahedral zirconia phase formed. Composite of HAP-ZrO2 =75:25 is the most suitable proportion because they still the highest hydroxyapatite content and all zirconia is in the tetrahedral phase